Perlindungan Hukum bagi Debitur atas Penetapan Harga Lelang yang Merugikan pada Pembiayaan Murabahah Kredit Pemilikan Rumah : Studi Kasus Putusan Nomor 71/Pdt.G/2025/PA.Smd - Ziana Walidah; Abdul Kadir Sabaruddin; Amsari Damanik (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The implementation of auction mechanisms for collateral in murabahah financing within Islamic banking institutions often raises legal issues, particularly regarding the determination of reserve auction prices that may disadvantage debtors. This study aims to analyze the determination of collateral auction prices in murabahah-based Home Ownership Financing (KPR) and examine the legal protection available to debtors in Decision Number 71/Pdt.G/2025/PA.Smd from the perspectives of justice and Islamic law. This research employs a normative juridical method using statutory, conceptual, and case approaches. The data sources consist of primary, secondary, and tertiary legal materials collected through library research and legal document analysis. The findings reveal that the determination of reserve auction prices for collateral in murabahah financing continues to generate legal disputes because the auction value is often considered inconsistent with the actual market value of the collateral. This condition may result in economic losses for debtors and indicates that the auction process does not fully reflect the principles of justice, transparency, and legal protection. From the perspective of maqāṣid al-sharī‘ah, collateral auctions should prioritize the protection of property (ḥifẓ al-māl) and prevent any form of injustice toward debtors. Furthermore, John Rawls’ theory of justice emphasizes the importance of protecting weaker parties in economic relationships. Therefore, greater transparency and objectivity in determining reserve auction prices are necessary to ensure fairness and legal certainty for all parties involved in murabahah financing disputes.